2011
DOI: 10.1055/s-0031-1280122
|View full text |Cite
|
Sign up to set email alerts
|

Vergleich klinischer und radiologischer Daten bei der Behandlung von Patienten mit osteoporotischen Wirbelkörper-Kompressionsfrakturen mit Radiofrequenz-Kyphoplastie oder mit Ballon-Kyphoplastie

Abstract: The RFK has proven to be a clinically very effective procedure that does somewhat better than BKP in long-lasting pain relief. No differences could be detected regarding improvement of functioning and the mean restoration of mid- and anterior vertebral height. As far as the safety aspect is concerned the RFK offers the advantage of a statistically significant lower proportion of cement extrusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 8 publications
(8 reference statements)
0
16
0
1
Order By: Relevance
“…Additionally, RF-TVA consistently showed a well-identified focal area of PMMA with an extensive peripheral zone of PMMA interdigitation, providing mechanical interlock into the adjacent intact trabecular matrix. Additionally, several retrospective studies of RF-TVA for treatment of VCFs have demonstrated consistent improvements in back pain severity and ODI and no procedural complications [1517]. The results of these studies and of the current prospective study provide increasing evidence that treatment with RF-TVA is optimized by the targeted delivery and interdigitation of ultrahigh viscosity RF-heated cement into the remaining trabeculae.…”
Section: Discussionmentioning
confidence: 53%
“…Additionally, RF-TVA consistently showed a well-identified focal area of PMMA with an extensive peripheral zone of PMMA interdigitation, providing mechanical interlock into the adjacent intact trabecular matrix. Additionally, several retrospective studies of RF-TVA for treatment of VCFs have demonstrated consistent improvements in back pain severity and ODI and no procedural complications [1517]. The results of these studies and of the current prospective study provide increasing evidence that treatment with RF-TVA is optimized by the targeted delivery and interdigitation of ultrahigh viscosity RF-heated cement into the remaining trabeculae.…”
Section: Discussionmentioning
confidence: 53%
“…We saw one case of adjacent vertebral fracture (2.2 %) during the follow-up examination after 12 months. This is a good result compared to the adjacent fracture rates of 0 -8 % for vertebroplasty and 25 -26 % for kyphoplasty (follow-up period of 3 -12 months) for stabilized osteoporotic vertebral compression fractures [10,27] and 0 -18 % [6, 28] for vertebroplasty and 2.9 -18 % for kyphoplasty (follow-up period of 9 -12 months) for stabilized tumorous vertebral fractures [6,17,28]. This may indicate a change in the biomechanics of a vertebral body stabilized with the Osseofix ® system compared to one stabilized exclusively with bone cement [11].…”
Section: Special Complicationsmentioning
confidence: 79%
“…There were 5 studies from Germany [8,9,24,26,27] and 1 study from USA. [25] The extracted studies included 2 RCTs, [9,24] 1 prospective cohort studies, [26] and 3 retrospective cohort studies. [8,25,27] Five studies were published in English while 1 was in German.…”
Section: Resultsmentioning
confidence: 99%
“…[8,25,27] Five studies were published in English while 1 was in German. [26] The majority of the included patients suffered from osteoporotic VCF, and meanwhile malignant and traumatic VCF were involved in a part of the studies. There was no significant difference in age and gender between the 2 groups ( P  > .05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation